COVID-19 cleaning protocol changes, experiences, and respiratory symptom prevalence among cleaning services personnel - Wilson, Amanda M.; Jung, Yoonhee; Mooneyham, Sydney A.; Klymko, Ivana; Eck, Josie; Romo, Carlos; Vaidyula, Vineeth R.; Sneed, Sam J.; Gerald, Lynn B.; Beamer, Paloma I. (Frontiers in Public Health, 2023)
Introduction Cleaning protocols were changed in response to the COVID-19 pandemic with unknown occupational health impacts. There is evidence that COVID-19 transmission risks from contaminated surfaces are low and that exposure to cleaning products can increase risks of work-related asthma. The study objective was to investigate relationships between reported COVID-19-related changes in cleaning protocols and prevalence of asthma-related respiratory symptoms for asthmatic and non-asthmatic janitors and maids. A secondary objective was to characterize experiences of respiratory symptoms associated with cleaning and barriers to personal protective equipment (PPE) use. Methods Employees from two Tucson-based maid service companies (approximately 30 personnel in total) and one Phoenix-based school district (>300 janitors/custodians) were invited to participate in a written survey and/or a one-on-one interview in Spanish or English. Fisher’s exact tests (α = 0.05) were used to test for statistically significant associations between reported respiratory symptoms by self-reported physician-diagnosed asthma status and changes in cleaning protocols. Interviews were transcribed and then analyzed by at least two researchers in English or Spanish. Results Eighty-three percent reported that cleaning protocols had changed during COVID-19, with the two most reported changes including increased cleaning frequency (92%) and change of application type (e.g., fog, spray, wipe) (53%). There was a statistically significant association between multiple respiratory symptoms and self-reported physician diagnosed asthma. Reporting a type of application change (e.g., fog, spray, wipe) and being awakened during the night by attack/episode of cough were statistically significantly associated (p = 0.04). Interviews elucidated respiratory issues related to fogging devices. Discussion This study provides preliminary evidence that changes in cleaning and disinfection protocols during COVID-19 (namely, the use of fogging/mechanical spraying devices) may have had negative impacts on the health of workers in the cleaning industry with little benefit to reducing COVID-19 risks. Further research is needed to evaluate the generalizability of our findings across larger geographical areas and to develop guidance for employers and employees on how to protect and promote respiratory health.